OK there are a few ways to solve this. Substitution may be the easiest. if y = 8x + 4 and 3y = 2x "something" 6 we can multiply the left equation by 3. so it becomes 3*y = (3*8)x + (3*4) or for simplicity 3y = 24x + 12 so if we have the other equation we get to replace things. if 3y = 24x +12 and 3y = 2x "something" 6. we can set the two things equal 24x + 12 = 2x "something" 6 so then just solve from there. Hope that helps. post or PM if you have any other questions or if you need more explanation.
= (-84/1) times (1/11) times (1/3) --- (you can rearrange it however you like it doesn't matter) = (-84/3)/11 = -28/11
So, x is -9/11 y is -28/11
If you don't get anything write it out on paper. Doing the problem/solution yourself is usually more helpful in making you understand it than doing mental mathematics, even if you're just copying it. As long as you try to understand it as you rewrite it, you'll get it.